Hibridación entre la danza urbana y la danza folclórica colombiana. Sistematización de Prácticas Pedagógicas Investigativas. (2023)
The present work aims to show and share the process carried out during the ‘Investigative pedagogical practices’ I, II and III of the Bachelor’s degree in Artistic education with an emphasis on Dance and Theater, with the group of young people from the Acto Kapital Cultural and Artistic Foundation, within the Kapital Dance Training School, whose participants are mainly Colombian folkloric dancers.